Analisis Jalur Kritis pada Supply Chain Management Pupuk Organik Cair di PT Alove Bali - SINAGA, CATHERINE ANASTASIA; DEWI, RATNA KOMALA; USTRIYANA, I NYOMAN GEDE (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism); Vol.5, No.1, Januari 2016, 2016)
Abstract Critical Path Analysis by Supply Chain Management of Organic Liquid Fertilizers at PT Alove Bali Competition fertilizer producers appear due to start the implementation of the organic agriculture system by the Government of Bali Province. PT Alove Bali are requested to maintain existence and the competitiveness sustainably in producing organic liquid fertilizer. An increase in the current activities can be done by supply chain management approachment. The purpose of this research is to analyze supply chain of organic liquid fertilizer, in terms of dimensions capabilities ,capacity, time and cost. Capabilities and capacity described in qualitative and quantitative to evaluate company cooperation with suppliers and consumers. The method of network analysis used for measuring the saving time one cycle production in critical path, and the cost saving. The results show that companies and partners run their rights and duties in accordance with procedures set forth in contract including cooperation agreement, funding assistance for supplier, the payment system, and evaluate aloevera supplier performance. Based on the capacity analysis, fertilizer sales of 6.57 percent the last three years and the 93,43 percent kept as fertilizer stock half finished. Based on the Project Evaluation Review Technique, the results show the efficient time to one cycle production is 2,382.28 hours and the cost went down to Rp 1,271,666.00. Keywords: Supply chain, Organic liquid fertilizer, Critical path analysis